Assessment of post-harvest handling of mango and evaluation of mango jam in major mango producing areas of South Omo Zone, SNNPR, Ethiopia (International Journal of Agricultural Research, Innovation and Technology, 2022)
The present study aimed to assess the postharvest handling practice, demonstrate and popularize mango jam processing on rural households’ levels in major mango growing areas of Debub Ari Woreda, South omo, Southern Ethiopia. Training manual was developed and Practical training on processing, post-harvest handling and utilization of mango jam was given for 12 DAs, 7 Administrators and 161 model Farmers comprising of 72 female farmers and 65 model male farmers and 40 model farmer households were interviewed about the technology and postharvest handling practice in the area in which 28 are females and 12 are male. Postharvest handling practice and sensory perception of mango jam and other relevant data were collected, analysed, interpreted and discussed. Results revealed that, 87.5% of respondent are greater than 25 years old and 40.0% attended various levels (elementary to high school) education. The major transportation method and packaging material used as replied by the respondents are 42.5% (use pack animals: donkey, mule and horse) and 47.5% (use sack), respectively. Pest attack (disease, insect) followed by mechanical damage during harvesting, poor packaging material and damage during transportation were identified as the main causes of mango loss specified by the respondents. Therefore, use of the better adapted and pest/disease-tolerant varieties, improved fruit production and harvesting practice, proper storage and transportation facilities, appropriate postharvest innovations and technologies are required to reduce postharvest loss and extend fruit shelf-life.Int. J. Agril. Res. Innov. Tech. 12(1): 155-160, June 2022